Prosthesis-Patient Mismatch Increases Early and Late Mortality in Low Risk Aortic Valve Replacement - Elmahdy, Walid; Osman, Mohamed; Farag, Mohamed; Shoaib, Ahmad; Saad, Haisam; Sullivan, Keith; Krishnan, Unni; Nashef, Samer; Berman, Marius (Seminars in thoracic and cardiovascular surgery, 2021)
The concept of prosthesis-patient mismatch (PPM) has gained much attention since first described 40 years ago. Previous studies have shown conflicting evidence regarding increased early and late morbidity and mortality with PPM after aortic valve replacement (AVR). The aim of this study was to evaluate the effects of PPM on short- and long-term mortality in low-risk patients after isolated AVR. A retrospective, single-center study involving 1707 consecutive patients ≤80 years of age with preserved left ventricular systolic function who underwent elective, primary isolated AVR operations from 2008 to 2018. Patients were stratified into 2 groups according to the presence of PPM (n = 96), defined as effective orifice area index <0.85 cm2/m2 body surface area, and no-PPM (n = 1611). The effect of PPM on mortality was evaluated with univariate and multivariate analyses. 30-day mortality was 0.8% (4.2% in PPM group vs 0.6 in no-PPM group; P = 0.005). PPM occurred more in female gender, obese and older patients. PPM was highly associated with long-term all-cause mortality (median 4 years [Q1–Q3 2–7]; HR: 1.79, 95% CI: 1.27–2.55, P = 0.002), and remained strongly and independently associated after adjustment for other risk factors (HR: 1.60, 95% CI: 1.10–2.34, P = 0.014). In propensity score-matched analysis, the adjusted mortality risk was higher in PPM group (HR: 2.03, 95% CI: 1.22–3.39, P = 0.006) compared to no-PPM group. In a single-centre observational study, PPM increased early mortality and was independently associated with long-term all-cause mortality after low-risk, primary isolated AVR operations. Strategies to avoid PPM should be explored and implemented. PPM was highly associated with long-term all-cause mortality. Small Aortic Valve Annulus MDT (SAVA-MDT) exploring options to prevent PPM, including the implantation of newer generation prosthetic valves, aortic root enlargement and TAVI, should be established. [Display omitted]